Effect of Methanolic Extract of Carica papaya Seed on Renal Function and Antioxidant Activities Following Ibuprofen-induced Toxicity on Male Wistar Rats - Okafor, Ani Celestine; Nonso, Ezeokafor Emmanuel; Obinna, Okolo Kenneth; Mark, Abayomi David; Luke, Nweke Maduka; Pearl, Okeke Adaobi; O’Brien, Chukwu JohnAja; Uchenna, Agu Francis; Ikenna, Agbor Joseph; Richard, Ndubuisi Nonso; Uche, Nwanaga Clinton; Mmesoma, Iheanacho Hannah; et al. (Free Radicals and Antioxidants)
In this study, the effect of methanolic seed extract of Carica papaya (MSECP) was investigated to ascertain its effect on the renal function and antioxidants activities following ibuprofen induced renal toxicity. Phytochemical screening of crude extract revealed the presence of alkaloids, flavonoids, glycosides, saponins and tannins while anthraquinone and phlobatannins were found to be absent. Thirty (30) healthy male Wistar rats were divided into 5 groups. Group A (received feed and water only); Group B received 80mg/kg of ibuprofen only; Group C received 80mg/kg of ibuprofen + 150mg/kg of MSECP; Group D received 80mg/kg of ibuprofen + 300mg/kg of MSECP; Group E (received 80mg/kg of ibuprofen and treated with 600mg/kg of (MSECP). The administration of the extract lasted for 21 days within hours of 7-8 am via oral gavage. After 21 days the animals were anesthetized with 25% Urethane and blood was collected using a heparinized capillary tube and transferred into a plain container and centrifuged. The serum retrieved was used to assay serum antioxidants Superoxide dismutase (SOD), Catalase activity (CAT), Glutathione (GSH), Glutathione peroxidase (GPX), Total Antioxidant capacity (TAC) and kidney enzymes (urea and creatinine). MSECP significantly reduced the plasma concentration of urea and creatinine (p>0.05) when compared to group A. The antioxidant enzymes reduced significantly (p>0.05) in groups that was administered with MSECP when compared to the group A and B. MSECP was discovered to have some therapeutic effect on renal function probably as a result of some of the antioxidants and phytonutrients present in Carica papaya which have the capability of increasing glomerular filtration of toxic substances from the kidney and hence recommend that Carica papaya seed could be included in our daily diet.
Keywords: Antioxidants; Carica papaya; Phytochemical; Oxidative stress